2017
DOI: 10.1002/anie.201704849
|View full text |Cite
|
Sign up to set email alerts
|

Native Desorption Electrospray Ionization Liberates Soluble and Membrane Protein Complexes from Surfaces

Abstract: Mass spectrometry (MS) applications for intact protein complexes typically require electrospray (ES) ionization and have not been achieved via direct desorption from surfaces. Desorption ES ionization (DESI) MS has however transformed the study of tissue surfaces through release and characterisation of small molecules. Motivated by the desire to screen for ligand binding to intact protein complexes we report the development of a native DESI platform. By establishing conditions that preserve non‐covalent intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…The recorded spectrum is dominated by 15+ to 17+ BSA ions, which is consistent with the finding of the native DESI work from Robinson's group. 28 However, the width of ion peaks in our native BSA study is found to be broader. Apart from the differences in resolving power afforded by a Q-ToF compared to an Orbitrap mass analyzer, we suggest that the broad peak width may also be a result of the non-desalting protein sample preparation method employed in our study.…”
Section: Solvent Filtering For Native Desimentioning
confidence: 50%
“…The recorded spectrum is dominated by 15+ to 17+ BSA ions, which is consistent with the finding of the native DESI work from Robinson's group. 28 However, the width of ion peaks in our native BSA study is found to be broader. Apart from the differences in resolving power afforded by a Q-ToF compared to an Orbitrap mass analyzer, we suggest that the broad peak width may also be a result of the non-desalting protein sample preparation method employed in our study.…”
Section: Solvent Filtering For Native Desimentioning
confidence: 50%
“…Analysis by high resolution MS revealed that the charge state distributions observed depend on the detergent used in the desorption plume, suggesting that on-surface detergent exchange was occurring. Moreover, specific binding to MPs could be observed by adding ligands to the desorption spray [128]. Excitingly, this opens up the possibility for the study of membraneembedded MPs on surfaces directly by DESI-MS.…”
Section: Alternative Ionization Methodsmentioning
confidence: 99%
“…2) [123,127]. Using DESI, MPs prepared in detergents and deposited onto glass surfaces could be desorbed by electrospraying a detergent-containing solution onto the surface [128]. Analysis by high resolution MS revealed that the charge state distributions observed depend on the detergent used in the desorption plume, suggesting that on-surface detergent exchange was occurring.…”
Section: Alternative Ionization Methodsmentioning
confidence: 99%
“…Clearly, DESI requires further investigation to develop our understanding for protein analysis and this is certainly a barrier to its adoption in routine or high-throughput analysis environments. One study has reported DESI for native protein analysis of purified proteins, successfully ionising large non-covalent complexes such as GroEL 14-mer [69]. Insoluble membrane proteins were also analysed by the addition of detergents to the DESI solvent system.…”
Section: Desorption Techniquesmentioning
confidence: 99%